2019
DOI: 10.1007/s00125-019-4822-4
|View full text |Cite
|
Sign up to set email alerts
|

Beta cells in type 1 diabetes: mass and function; sleeping or dead?

Abstract: Histological analysis of donor pancreases coupled with measurement of serum C-peptide in clinical cohorts has challenged the idea that all beta cells are eventually destroyed in type 1 diabetes. These findings have raised a number of questions regarding how the remaining beta cells have escaped immune destruction, whether pools of ‘sleeping’ or dysfunctional beta cells could be rejuvenated and whether there is potential for new growth of beta cells. In this Review, we describe histological and in vivo evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 79 publications
5
88
0
1
Order By: Relevance
“…Our results suggest that the natural evolution of the β cell-specific CD8 + T cell response during the prediabetic period in young children becomes increasingly dominated by end-stage cytolytic effector cells which are capable of directly mediating β cell destruction. These data fit with observations that at clinical diagnosis β cell destruction is already well advanced [84]. Of interest, previous studies of the DIPP cohort have reported that the HLA-A*24 allele is associated with accelerated disease progression from seroconversion to clinical disease [26].…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that the natural evolution of the β cell-specific CD8 + T cell response during the prediabetic period in young children becomes increasingly dominated by end-stage cytolytic effector cells which are capable of directly mediating β cell destruction. These data fit with observations that at clinical diagnosis β cell destruction is already well advanced [84]. Of interest, previous studies of the DIPP cohort have reported that the HLA-A*24 allele is associated with accelerated disease progression from seroconversion to clinical disease [26].…”
Section: Discussionsupporting
confidence: 88%
“…With the identification of persistent proinsulin processing in individuals with undetectable C-peptide, it is intriguing to ask whether other β cell populations are dysfunctional enough to be considered merely dormant (18). How the surviving β cells managed to elude autoimmune destruction and whether these other groups of dormant β cells could be rejuvenated remain important questions (19).…”
Section: Discussionmentioning
confidence: 99%
“…Together, this suggests that β‐cell loss could be overestimated in T2D and rather it is changes in β‐cell phenotype and function which are more important in the diseases pathogenesis (Marselli et al., 2014). In a similar fashion, β‐cell loss in T1D may also be linked to an increase in dysfunctional β‐cells (Oram, Sims, & Evans‐Molina, 2019). For example, β‐cell dedifferentiation is another mechanism linked to β‐cell failure (Talchai, Xuan, Lin, Sussel, & Accili, 2012).…”
Section: Effect Of Exercise On β‐Cell Massmentioning
confidence: 96%